SPAD timing jitter modeling using Fourier series - Eyvazi, Kaveh; Karami, Mohammad Azim (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
In this paper, a simple analytical model for the Gaussian’s peak response part of the timing jitter of single photon avalanche diodes (SPADs) is proposed using Fourier series in the multiplication time calculation. The multiplication time characterizes avalanche multiplication process speed in which low multiplication time suggests a swifter response time and a higher avalanche speed. This paper presents an analytical solution which results in a more accurate multiplication time. The model is verified for SPADs implemented in 0.15 and 0.18 μm standard CMOS process, and the accuracy of the proposed analytical method in full-width at half-maximum (FWHM) calculation is improved by 25% and 5% with respect to the numerical model, respectively.
Optica Applicata, Vol. 53, 2023, nr 2, s. 239-248
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; analytical models; Fourier series; multiplication time; timing jitter